High precision measurement of light polarization using a Cs atomic magnetometer configuration. (17th May 2021) - Peng, Xinxin; Zhou, Yinmin; Li, Lianhua; Xu, Zhengyi; Zhou, Min; Xu, Xinye
Abstract: The polarization of light affected by the birefringence of optical elements, such as vapor cell walls, mirrors, and windows, may introduce systematic errors that can be minimized by precisely measuring and correcting the light polarization with a highly sensitive atomic polarimeter. In high precision measurements, it is necessary to measure the light polarization with a high precision where the light interacts with atoms. However, it is inconvenient or even impossible to use the presented method to measure the light polarization, for example, in a cell or cavity. We present a precise and relatively straightforward method to measure the light polarization based on a cesium (Cs) atomic magnetometer configuration. The pump-probe scheme is involved in our experiment. The pump light polarizes atomic spins and the probe light measures the spins polarization. The optical rotation of the probe light significantly depends on the pump light ellipticity, which can be used to measure the light polarization with a high precision. In our work, we present a method to measure the pump light ellipticity with a sensitivity of 2.1 × 10 −8 rad Hz −1/2 for linearly polarized light, which has approximately an order of magnitude improvement than previous research results.